The Use of Tell Me More (TMM) in Learning Vocabulary Among ESL Students - Zuraina, Ali; Jayakaran, Mukundan; Ahmad Fauzi, Mohd Ayub; Roselan, Baki (2011)
This study examines the use of Tell Me More (TMM) software among tertiary students in Universiti Malaysia Pahang (UMP). The research questions addressed in the study are as follows: (1) Is there any significant difference in the number of words learnt between the Pre-test and the Delayed Recall post-test using TMM among students? (2) How are the students’ learning attitudes after TMM is used in learning vocabulary? (3) Why do students prefer using TMM in learning vocabulary?, and (4) Why do students find difficult using TMM in learning vocabulary? The seven-week study involved 43 subjects attending two vocabulary lessons. Interviews and survey are also administered in the study. Results shows that there is significantly higher scores in the Delayed Recall post-test (M = 18.27, SD = 4.461) than the Pre-test (M= 13.46, SD = 4.460), t (42) = -5.707, p = .000 in using TMM to learn vocabulary. In relation to learning attitudes, the descriptive analysis demonstrates that students claim that they have good opportunity using TMM, yet their perceptions of learning vocabulary remain the same as before they used the software. Qualitative findings reveal that students prefer the drag-and-drop feature in TMM. However, their experiences also show the difficulties of using the software such as imitating the native-speaker in pronouncing words, absent of flexible access and unavailability of hypertext for meaning of target words. These findings provide empirical data for the use of computers in learning vocabulary, yet, their benefits depend on the individual learners.